Protective efficacy of Ad26.COV2.S against SARS-CoV-2 B.1.351 in macaques - Yu, Jingyou; Tostanoski, Lisa H.; Mercado, Noe B.; McMahan, Katherine; Liu, Jinyan; Jacob-Dolan, Catherine; Chandrashekar, Abishek; Atyeo, Caroline; Martinez, David R.; Anioke, Tochi; Bondzie, Esther A.; Chang, Aiquan; et al. (Nature (London), 2021)
The emergence of SARS-CoV-2 variants that partially evade neutralizing antibodies poses a threat to the efficacy of current COVID-19 vaccines 1 , 2 . The Ad26.COV2.S vaccine expresses a stabilized spike protein from the WA1/2020 strain of SARS-CoV-2, and has recently demonstrated protective efficacy against symptomatic COVID-19 in humans in several geographical regions—including in South Africa, where 95% of sequenced viruses in cases of COVID-19 were the B.1.351 variant 3 . Here we show that Ad26.COV2.S elicits humoral and cellular immune responses that cross-react with the B.1.351 variant and protects against B.1.351 challenge in rhesus macaques. Ad26.COV2.S induced lower binding and neutralizing antibodies against B.1.351 as compared to WA1/2020, but elicited comparable CD8 and CD4 T cell responses against the WA1/2020, B.1.351, B.1.1.7, P.1 and CAL.20C variants. B.1.351 infection of control rhesus macaques resulted in higher levels of virus replication in bronchoalveolar lavage and nasal swabs than did WA1/2020 infection. Ad26.COV2.S provided robust protection against both WA1/2020 and B.1.351, although we observed higher levels of virus in vaccinated macaques after B.1.351 challenge. These data demonstrate that Ad26.COV2.S provided robust protection against B.1.351 challenge in rhesus macaques. Our findings have important implications for vaccine control of SARS-CoV-2 variants of concern. SARS-CoV-2 challenge of rhesus macaques demonstrates that the Ad26.COV2.S vaccine induces robust protection against both the WA1/2020 isolate and the B.1.351 variant of concern.